Improvement of DC Fault Current Limiting and Interrupting Operation of Hybrid DC Circuit Breaker Using Double Quench - Sang-Jae Choi; Jun-Hyup Lee; Jin-Wook Lee; Sung-Hun Lim (Energies, 2021)
In this paper, direct current (DC) fault current limiting and interrupting operation of hybrid DC circuit breaker (DCCB) using double quench, which consists of DCCB, a series resonance circuit, power electronic switch, surge arrestor, two separated current limiting reactor/resistor, and two superconducting elements, were suggested. The suggested hybrid DCCB can perform the interrupting operation after twice or once DC fault current limiting operation according to DC fault current amplitude. To verify the effective operation of the suggested hybrid DCCB, the modeling for the components of DCCB, the surge arrestor, and the SCE was carried out and its DC operational characteristics were analyzed. Through the analysis of the modeling results for the suggested hybrid DCCB, the advantages of hybrid DCCB were discussed.